2018
DOI: 10.9755/ejfa.2018.v30.i5.1683
|View full text |Cite
|
Sign up to set email alerts
|

Determination of pesticides residues in quinoa (Chenopodium quinoa Willd) using QuEChERS and LC-MS/MS

Abstract: The QuEChERS method was optimized and validated for the determination of 40 pesticides in 37 samples of quinoa from the harvest 2010-2011 in Puno - Peru. The method involves extraction with 1% acetic acid acetonitrile with CH3COONa anhydrous and MgSO4 followed by dispersive solid-phase extraction with PSA and C18. Analyses were performed with LC-MS/MS using C18 column 150 mm x 2.1 x 3.5 µm, water and acetonitrile 0.1% formic acid used as mobile phase. Spiked quinoa blank at 0.01 and 0.1 mg kg-1 was employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…compounds in food products, flowers, fruits and vegetables (Vilca et al 2018). Lentola et al (2017) showed that many ornamental plants are also treated with systemic pesticides prior to purchase and there is little information as to whether these pesticides persist in plant tissues long enough to contaminate pollen during flowering after purchase.…”
Section: Introductionmentioning
confidence: 99%
“…compounds in food products, flowers, fruits and vegetables (Vilca et al 2018). Lentola et al (2017) showed that many ornamental plants are also treated with systemic pesticides prior to purchase and there is little information as to whether these pesticides persist in plant tissues long enough to contaminate pollen during flowering after purchase.…”
Section: Introductionmentioning
confidence: 99%